+0  
 
+1
92
2
avatar+270 

Thanks in advance!

 

 May 13, 2020
 #1
avatar+111456 
+1

We can use  the  tangent-secant theorem here

 

This says that  the square  of the tangent segment  =   the length of the external part of the secant segment * the  length of the secant 

 

We  have  that

 

8^2  =  4 ( 4 +x)  simplify

 

64  = 16 + 4x      subtract  16 from both sides

 

48 = 4x     divide both sides by 4

 

12  =  x

 

 

cool cool cool

 May 13, 2020
 #2
avatar+270 
+1

Thanks CPhill!

Mathisgood  May 13, 2020

71 Online Users

avatar
avatar